Global patterns of carnivore spatial ecology research in agroecosystems - Curveira-Santos, Gonçalo (2022)
The growing needs for agricultural expansion and intensification will likely continue to reduce and fragment the terrestrial habitats fundamental to mammalian carnivores. Recent research identified benefits of agroecosystems to carnivores recognizing their multifunctionality, mostly for common species. However, the variability of carnivore ecology investigated in agroecosystems, biases in agriculture types and species targeted, and methodological approaches may affect the available knowledge to reconcile conservation and agricultural production. To fill this gap, we conducted a systematic literature review to identify which aspects of and how is carnivore spatial ecology being investigated within agroecosystems. Of the 110 reviewed studies, most focused on agricultural crops (55%) and grasslands (47%) and half referred to monocultures. We found that 61% of the studies were conducted in Europe and North America. Eighty-four carnivore species were studied, 73% classified as Least Concern, with 67% of the studies targeting a single species and 30% focused on only seven common species. Almost all studies included some form of habitat use analysis and species’ home-range and its attributes (e.g. size, resource selection), the most common spatial ecology aspects studied. Most studies suggested that agriculture functions as food provisioning (69%) but few used direct food availability measures. Our results highlight that studies tend to be descriptive and geographically biased towards northern hemisphere and to non-forested agricultural types. We suggest that future carnivore spatial ecology research in agroecosystem should be hypotheses-driven, with greater focus on the mechanisms and processes through which agroecosystems might affect carnivore spatial ecology in particular for areas with high priority for carnivore conservation.